The Portrayal of Belgrade in the Prose of Stevan Sremac - Soleša, Biljana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The subject of research is the portrayal of Belgrade in the prose of Stevan Sremac. The introductory part of the paper refers to the socio-historical, economic and cultural circumstances in Belgrade in the late 19th century, as well as general characteristics of the Belgrade prose by Sremac. The interpretation of selected stories with this theme is given in the central part of the work, it highlights the typical motifs of intertwining of the natives and the immigrants, rural and city mentality, typical motifs of taverns, and the city suburbs. The paper discusses the themes of Greek-Aromanian community in Belgrade, the emergence of the Belgrade bourgeoisie and the bureaucratic system. There is a reflection on the artistic portrayal of others and us, and on the image of national types. An insight into the critical and satirical aspect of this prose, in the final part of his work, reveals that the author created certain topics within the Belgrade prose that deal with predominantly social issues with an artistic process that lacks buoyancy or humour, which Sremac is known for to the wider audience.